Fundamentals of oil & gas accounting - Wright, Charlotte J. (PennWell, 2017)
Professor updates her indispensable accounting book for the oil and gas industry in this revised and expanded Sixth Edition. The past several years have seen significant changes in the accounting and disclosure rules for the industry. While the book has thorough updates throughout, there are new industry issues specifically addressed from the accounting perspective. Some of the significant updates and new material include: Discussion of the significance of shale and unconventional production as it relates to accounting principles; New definitions of reserves from the Securities and Exchange Commission, and the impact on accounting processes; All citations and references align with the updated authoritative literature from the Financial Accounting Standards Board; A new chapter discussing specific issues previously unaddressed regarding property valuation in the industry; New, and updated, end-of-chapter problems.
Revised edition of Fundamentals of oil and gas accounting, 2008.
Keywords: Petroleum industry and trade -- Accounting.; Gas industry -- Accounting.; elektronické knihy; electronic books